Fistful of dollars [videorecording (DVD)] - Eastwood, Clint, 1930-; Koch, Marianne, 1931-; Volonté, Gian Maria, 1933-1994 (Clint Eastwood collection., 2011)
A mysterious gunman has just arrived in San Miguel, a grim and dusty border town where two rival bands of smugglers are terrorizing the impoverished citizens. A master of the "quick-draw", the stranger soon receives lucrative offers of employment from each gang.